Colorectal cancer A prospective baseline study population in the city of Montevideo: Preliminary results of the incidence study - Carriquiry, Luis; Piñeyro, Alberto; Maggiolo, José F; Palacio, José L; Leites, Alejandro; Vivas, Carlos; Neirotti, Rubens; Caviglia, Pablo; Ihlenfeld, Juan; Canessa, César; Fernández, Ricardo; Taruselli, Roberto; et al. (Cirugía del Uruguay, 1995)
Uruguay shares with Argentina the dubious honour of being the only South Amercan countries with a high incidence of colorectal cancer. The present study is the first population-based study of co/orectal cancer in Montevideo. Through multiple--access searching strategy, ali new cases of colorectal cancer diagnosed in inhabitants of Montevideo during 1991 were carefully registered, in arder to achieve a proper knowledge about incidence, clinical presentation, diagnostic methods, treatment and clinico--pathologica/ staging. 554 patients with newly diagnosed adenocarcinomas of the colorectum were identified, with a male-female relationship of 1:1,07 and an average age of 69 years. 24% presented as an emergency, mainly as intestinal obstruction. 63% were colonic tumours (49% in right colon and 51% in left colon) and 37% were rectal tumours. Syncronic hepatic metastasis were found in 16,8%, isolated perifonea/ carcinomatosis in 5,4% and extension of /he tumour to adyacent structures in 13,9%. 527 patients were operated (95,2%) with postoperative mortality of 11,8%, and resection of /he tumour was done in 475 patients (a resecability rate of 86%) with a 10,8% postresection mortality. 3,4% of the coloree/al cancers were metachronous and 1,9 synchronous. Analysis of these data revealed: 1) that registering methodology was basically appropiate; 2) that the main clinical and pathological traits of coloree/al cancer in Montevideo are not different from /hose resulting of o/her population based on large unselected series in North America, Australia or Western Europe.